Electrical Transport Anisotropy Controlled by Oxygen Vacancy Concentration in (111) LaAlO3/SrTiO3 Interface Structures. Issue 3 (2nd December 2016) - Davis, Samuel Kenneth; Huang, Zhen; Han, Kun; Ariando,; Venkatesan, Thirumalai; Chandrasekhar, Venkat
Abstract : The anisotropy in the electronic properties at the conducting 2D interface of (111) LaAlO3 and SrTiO3 can be tuned by post‐growth treatment. This treatment strongly tunes the dependence of the device resistance, carrier concentration, and directional anisotropy on the in situ electrostatic back‐gate voltage. The effects are attributed to the changes in the oxygen vacancy concentration at the interface.